Carbon allocation of Spirodela polyrhiza under boron toxicity - Pagliuso, Débora; Pedro de Jesus Pereira, João; Ulrich, João Cristiano; Barbosa Cotrim, Marycel Elena; Buckeridge, Marcos S.; Grandis, Adriana (Frontiers in Plant Science, 2023)
Pectic polysaccharides containing apiose, xylose, and uronic acids are excellent candidates for boron fixation. Duckweeds are the smallest plants with a fast-growing capacity that can absorb diverse metals and contaminants from water and have high pectin content in their cell walls. Therefore, these plants can be considered excellent boron (B) accumulators. This work aimed to investigate the relationship between B assimilation capacity with apiose content in the cell wall of Spirodela polyrhiza subjected to different boric acid concentrations (from 0 to 56 mg B.L-1). The results showed that B altered the morphology and carbohydrate composition of this species during plant development. The optimum B concentration (1.8 mg B.L-1) led to the highest relative growth and biomass accumulation, reduced starch, and high pectin and apiose contents, together with increased expression of UDP-apiose/UDP-xylose synthase (AXS) and 1,4-α-galacturonosyltransferase (GAUT). The toxic state (28 and 56 mg B.L-1) increased the hexose contents in the cell wall with a concomitant reduction of pectins, apiose, and growth. The pectin content of S. polyrhiza was strongly associated with its growth capacity and regulation of B content within the cells, which have AXS as an important regulator. These findings suggest that duckweeds are suitable for B remediation, and their biomass can be used for bioenergy production.